2006
DOI: 10.1038/sj.ijo.0803453
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the metabolic syndrome in Zhejiang Chinese obese children and adolescents and the effect of metformin combined with lifestyle intervention

Abstract: Objective: We aimed to evaluate the prevalence of metabolic syndrome (MS) in a group of obese children and adolescents in Zhejiang in the south of China, and to compare risk factors such as insulin resistance, adiponectin level and impaired glucose tolerance (IGT) etc with that of simple obese group (SOB) and non-obese healthy group, and also to evaluate the effect of metformin and lifestyle intervention in MS group by up to a 3-month follow-up. Methods: Three hundred and forty eight moderately or severely obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 34 publications
3
42
0
5
Order By: Relevance
“…31 Obesity, MetS prevalence and associated risk factors in children and adolescents have increased dramatically over decades. [1][2][3]12,[32][33][34] A previous study of our team concluded that half of the Balearic Islands' adolescents had at least one of the MetS components and a significant number of them, especially the obese, had MetS, 31 showing an emerging health problem in this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Obesity, MetS prevalence and associated risk factors in children and adolescents have increased dramatically over decades. [1][2][3]12,[32][33][34] A previous study of our team concluded that half of the Balearic Islands' adolescents had at least one of the MetS components and a significant number of them, especially the obese, had MetS, 31 showing an emerging health problem in this region.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 This increase is noted even in children. 3 The features of MetS include central obesity, insulin resistance, hyperglycaemia, dyslipidaemia (increased triglyceride and decreased high-density lipoprotein) and hypertension, all risk factors for cardiovascular disease and type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 98%
“…12 Nonetheless, the three proposed definitions have been used in several studies carried out in pediatric populations, which reported high-prevalence of the MS in obese children and adolescents. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The results of these studies varied according to the selected diagnostic criteria used, as established by a recent comparison study. 34 Moreover, in an evaluation of the different prevalence yields using different definition, Goodman et al 35 found that ATP III definition identified half as many children and adolescents as having MS as did WHO definition in the same population.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of Chinese obese youth found that Metformin, in combination with a low-fat diet and 30 min of moderate-intensity aerobics, improved clinical symptoms of MetS. 45 Therefore, the significance of each part of the intervention cannot be determined.Another problem related to the independent effect of training and fitness on MetS is that it may be very difficult to train without changing body composition. Loss of weight can improve the ability to exercise.…”
mentioning
confidence: 99%